Plant responses to abiotic stress regulated by histone acetylation - Wang, Fei; Li, Chong-Hua; Liu, Ying; He, Ling-Feng; Li, Ping; Guo, Jun-Xin; Zhang, Na; Zhao, Bing; Guo, Yang-Dong (Frontiers in Plant Science, 2024)
In eukaryotes, histone acetylation and deacetylation play an important role in the regulation of gene expression. Histone acetylation levels are reversibly regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs). Increasing evidence highlights histone acetylation plays essential roles in the regulation of gene expression in plant response to environmental stress. In this review, we discussed the recent advance of histone acetylation in the regulation of abiotic stress responses including temperature, light, salt and drought stress. This information will contribute to our understanding of how plants adapt to environmental changes. As the mechanisms of epigenetic regulation are conserved in many plants, research in this field has potential applications in improvement of agricultural productivity.